2020
DOI: 10.1186/s12864-020-6566-4
|View full text |Cite
|
Sign up to set email alerts
|

Presence–absence polymorphisms of single-copy genes in the stony coral Acropora digitifera

Abstract: Background: Despite the importance of characterizing genetic variation among coral individuals for understanding phenotypic variation, the correlation between coral genomic diversity and phenotypic expression is still poorly understood. Results: In this study, we detected a high frequency of genes showing presence-absence polymorphisms (PAPs) for single-copy genes in Acropora digitifera. Among 10,455 single-copy genes, 516 (5%) exhibited PAPs, including 32 transposable element (TE)-related genes. Five hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The polymorphic sites indicated the differences between individuals within one species (Jaratlerdsiri et al 2014;Viscardi et al 2018;Brodetzki et al 2019;Takahashi-Kariyazono et al 2020). The research on several mitochondrial genes also showed some intra-population variation, and their differences were used as genetic markers (barcode species) (Li et al 2008;Meenakshi et al 2010;Yaacov et al 2012;Wolff et al 2014;Naim et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphic sites indicated the differences between individuals within one species (Jaratlerdsiri et al 2014;Viscardi et al 2018;Brodetzki et al 2019;Takahashi-Kariyazono et al 2020). The research on several mitochondrial genes also showed some intra-population variation, and their differences were used as genetic markers (barcode species) (Li et al 2008;Meenakshi et al 2010;Yaacov et al 2012;Wolff et al 2014;Naim et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A type of genetic variants, presence–absence variants (PAVs), is represented by genes present in some genomes but absent in others within the same species ( 14 ). PAV genes might be fast-evolving genes, as they are able to reflect gene birth or death ( 22 ). In addition, PAV genes may contribute to adaptation to changing environments, including pathogen infection, antitumor-agent synthesis or disease resistance in plants as well as immunity in animals ( 15–19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted from three A. digitifera and two A. tenuis individuals from our previous study 18 , 19 . Genomic DNA from single colonies of M. informis and M. aequituberculata were provided by Dr. Masayuki Hatta.…”
Section: Methodsmentioning
confidence: 99%
“…Four primer sets are capable of amplifying the target sequence when the template genomic DNA does not contain an inversion of the sacsin-like gene, and six primer sets are capable of amplifying the target sequence when the template genomic DNA does not contain an inversion of the sacsin-like gene were used for PCR analysis (Table S3–4 ). To check the quality of genomic DNA, a primer set (34639_F1/34639_R1) 19 was used to amplify elongation factor 1-alpha: LOC107334639 as a positive control. The PCR conditions were as follows: denaturation step for 1 min 30 s at 93 °C, followed by 35 cycles of denaturation for 30 s at 93 °C, annealing for 3 min (PCR#1,2,8 and a positive control) or 8 min (PCR#3–7,9 and 10) at 55 °C, and extension for 10 min at 72 °C.…”
Section: Methodsmentioning
confidence: 99%